Pole to pole: the deep-sea king crab Lithodes couesi (Decapoda: Lithodidae) in the Burdwood Bank, Southwestern Atlantic Ocean - Pérez Barros, Patricia (2019)
In recent years, remote exploration around the Scotia Arc and waters off the Antarctic Peninsula yielded new records of Lithodidae suggesting our knowledge on their distribution is biased by our ability to sample areas with difficult access. In the present study, we used molecular methods to identify and report the occurrence of the deep-sea king crab Lithodes couesi, so far reported as a North Pacific lithodid, in the marine protected area (MPA) Namuncurá/Burdwood Bank II, Southwestern Atlantic Ocean; more than 10,000 km away from its known distribution. Our finding suggests that the distributions of deep-water lithodid species are more extensive than they have been previously thought. We emphasize the need for a worldwide key to identify lithodid species, and prompt to barcoding specimens, at least those from poorly known species or remote locations, in order to corroborate their specific status. Finally, our study stresses the importance of MPAs in the conservation of biodiversity, as well as the processes involved in its evolution.